Determination of Teacher Performance in Improving Education Quality in the Pandemic Era - Fadhlansyah, Muhammad; Indupurnahayu, Indupurnahayu; Firdaus, Muhammad Aziz (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Determining Teacher Performance to Improve the Quality of Education in the Pandemic Era. The problem that is used as the object of research is teacher performance which is seen to have decreased due to the change in the learning system from offline to online. This can cause the quality of education to decline. This research aims to analyze: 1). The Influence of Internal Factors on Teacher Performance. 2). The influence of internal factors on the quality of education. 3). The influence of external factors on teacher performance. 4). The influence of external factors on the quality of education. 5). The influence of teacher performance on the quality of education. 6). The influence of internal factors on the quality of education is mediated by teacher performance. 7). The influence of external factors on the quality of education is mediated by teacher performance. The data collection technique was using a questionnaire given to 85 respondents (teachers) from 3 schools, namely SMA Al Adzkar, SM AI Sinar Cendikia and Sekolah Alam Bintaro. The hypothesis used is Smart PLS ( Partial Least Square ). The research results show that: 1). The statistical value of internal factors on performance is 3.116 with a p value of 0.00 2 and a p value of less than 0.05, so it has a positive effect on teacher performance. 2). The statistical t value of internal factors on the quality of education is 3.277, the p value is 0.001 and the p value is more than 0.05, then positive influence on the quality of education. 3). The statistical t value of external factors on teacher performance is 2.561 with a p value of 0.011 or less than 0.05, so it has a positive effect on teacher performance. 4). The statistical value of external factors on the quality of education is 3.920 with a p value of 0.000 or a p value of more than 0.05, so it has a positive effect on the quality of education. 5). The statistical t value of teacher performance on the quality of education is equal to a p value of 0.022, so teacher performance has a positive effect on the quality of education. 6). The VAF value is 0.598, this shows that teacher performance is a partial mediator in the relationship between internal factors and the quality of education. 7). The VAF value is 0.631, this shows that teacher performance is a partial mediator in the relationship between external factors and the quality of education. The research conclusion is that, 1). There is a positive and significant influence of f actors internal on teacher performance. 2). There is a positive and significant influence of internal factors on the quality of education. 3). There is positive and significant influence external factors on teacher performance. 4) There is a positive and significant influence external factors on the quality of education. 5). There is a positive and significant influence on teacher performance to quality of education. 6) There is a positive and significant influence between internal factors on the quality of education with teacher performance as mediation. 7). There is a positive and significant influence between external factors on the quality of education and teacher performance as mediation.